X=4
Step 1: Simplify both sides of the equation.
1.5(x+4)-3=4.5(x-2)
(1.5)(x)+(1.5)(4)+ -3 =(4.5)(x)+(4.5)(-2)
(1.5x) + ( 6+-3) =4.5x - 9
(Combine like terms)
1.5x+3=4.5x-9
Step 2: Subtract 4.5x from both sides.
1.5x +3 -4.5x =4.5x=-9-4.5x-3x+3=-9
Step 3: Subtract 3 from both sides.
-3x+3-3=-9-3
-3x=12
Step 4: Divide both by -3
-3x/-3=-12/-3
X=4
Answer:
15
Step-by-step explanation:
f(x) = 5x + 40
…………………………
when x = -5
f(-5) = 5(-5) + 40
= -25 + 40
= 40 - 25
= 15
Answer:
is the answer 0
Step-by-step explanation:
Answer:
7519 is already in the simplest form. It can be written as 3.947368 in decimal form (rounded to 6 decimal places).
Step-by-step explanation: